2013
DOI: 10.3389/fnint.2013.00084
|View full text |Cite
|
Sign up to set email alerts
|

From ear to uncertainty: vestibular contributions to cognitive function

Abstract: In addition to the deficits in the vestibulo-ocular and vestibulo-spinal reflexes that occur following vestibular dysfunction, there is substantial evidence that vestibular loss also causes cognitive disorders, some of which may be due to the reflexive deficits and some of which are related to the role that ascending vestibular pathways to the limbic system and neocortex play in spatial orientation. In this review we summarize the evidence that vestibular loss causes cognitive disorders, especially spatial mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 155 publications
4
71
0
1
Order By: Relevance
“…For the space perception subscale, the absence of significant difference was surprising. The Cronbach's alphas showed a good internal consistency (0.821), and we would have expected a significant difference between vertigo and non-vertigo participants based one the previous literature (see [62] for an extensive review). There are a number of explanations that can explain the lack of effect for the space perception subscale.…”
Section: Discussionmentioning
confidence: 95%
“…For the space perception subscale, the absence of significant difference was surprising. The Cronbach's alphas showed a good internal consistency (0.821), and we would have expected a significant difference between vertigo and non-vertigo participants based one the previous literature (see [62] for an extensive review). There are a number of explanations that can explain the lack of effect for the space perception subscale.…”
Section: Discussionmentioning
confidence: 95%
“…Use of the Morris Water Task in rodents revealed that vestibular failure causes an impairment of spatial memory and navigation [1,2]. Human studies of patients with bilateral vestibular loss also exhibited significant spatial memory deficits associated with a bilateral hippocampal atrophy [3].…”
Section: Dear Sirsmentioning
confidence: 97%
“…Some even report feeling ashamed to be seen in public as others often think they are drunk. Moreover, due to multifocal cortical and thalamic projections of vestibular afferents, emotions, memory, cognitive abilities and personality can also be affected [3,4,5]. In most cases, a BVL cannot be compensated and sensory substitution is insufficient so that there is no or little spontaneous improvement to be expected in the long term [6].…”
Section: Introductionmentioning
confidence: 99%